Correction: Visible-light photooxidation in water by 1O2-generating supramolecular hydrogels. Issue 22 (29th May 2020) - Biswas, Sankarsan; Kumar, Mohit; Levine, Andrew M.; Jimenez, Ian; Ulijn, Rein V.; Braunschweig, Adam B.
Abstract : Correction for 'Visible-light photooxidation in water by 1 O2 -generating supramolecular hydrogels' by Sankarsan Biswas et al., Chem. Sci., 2020, 11, 4239–4245, DOI: ; 10.1039/C9SC06481H .